7.9k views
3 votes
Solve for x in the equation ]x^{2} - 12x + 59 = 0

User Labue
by
5.5k points

2 Answers

7 votes

Answer:

Solution for x:


6+√(23)i and
6-√(23)i

Explanation:

Given:
x^2-12x+59=0

It is quadratic equation and to solve for x.

using quadratic formula:


x=(-b\pm√(b^2-4ac))/(2a)

where, a=1, b=-12 and c=59

Put the values into the formula


x=(12\pm√(12^2-4\cdot 1\cdot -59))/(2(1))


x=(12\pm √(-92))/(2)

As we know,
√(-1)=i


x=6\pm√(23)i

Exact value of x :
6+√(23)i and
6-√(23)i

User Themiurgo
by
5.5k points
1 vote

Step-by-step explanation:


x^(2) - 12x + 59 = 0

Given equaiton is in the form of ax^2 +bx+c=0

we apply quadratic formula to solve for x


x= (-b+-√(b^2-4ac) )/(2a)

a= 1 b = -12 and c= 59


x= (12+-√((-12)^2-4(1)(59)))/(2(1))


x= (12+-√(92))/(2)


x= (12+-2√(23))/(2)

Divide the 12 and square root terms by 2


x=6+-√(23)

so
x=6+√(23) and
x=6-√(23)




User Farshid Rezaei
by
5.3k points